Environmental audit as a tool for sustainable development (international and domestic experience) - Berezovskyi, O. I.; Березовський, Олександр Іванович (Харківський національний автомобільно-дорожній університет, 2025)
The article examines the role of environmental auditing as an effective tool for ensuring sustainable development at both national and international levels. It analyzes key approaches and methodologies for conducting environmental audits and presents examples of international experience alongside domestic practices. The advantages and challenges of implementing environmental auditing in Ukraine are identified. The author concludes on the necessity to improve the regulatory framework and to intensify practical measures to enhance environmental safety and sustainable use of natural resources.
Екологічний аудит як інструмент сталого розвитку (міжнародний та вітчизняний досвід)
Keywords: environmental audit; sustainable development; environmental protection; international experience; regulatory framework; Ukraine; екологічний аудит; сталий розвиток; міжнародні стандарти; законодавство України; ISO 14001; екологічне управління; 658.5; 10.30977/BUL.2219-5548.2025.110.0.41